Sosialisasi Dan Pendampingan UMKM Desa Bareng Kecamatan Bareng Kabupaten Jombang Dalam Pembuatan NIB Dengan Brand Equity Melalui Logo Dan Arah Panah - Ellisa Adelia; Rizky Dermawan (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Socialization is a very useful thing in raising and conveying positive values to individuals, the socialization process is education through individual understanding and acceptance of the connections that occur in an activity that can provide input and output feedback. Learning from the monetary crisis that occurred in Indonesia in 1997-1998 which was marked by the decline in the joints of the economy caused by the rupiah exchange rate falling or dropping drastically against the dollar exchange rate. In 1998 many big entrepreneurs fell in Indonesia, but MSMEs were still able to survive and even increased in number. In this way, UMKM contribute to supporting the economy of a country so that the existence of UMKM is highly expected in the development and progress of the country's economy and is able to absorb the number of unemployed. In this background, MSMEs can be used as a part in expanding employment opportunities, play a role in the formation of the Gross Domestic Product (GDP) and increase foreign exchange earnings for the country of Indonesia because its market can reach national to international. Bareng Village, Bareng District, Jombang Regency is an agricultural producing village in the form of rice, corn, sugar cane, soybeans, vegetables, chilies and others. The livelihoods of the majority of the population are farmers, self-employed, and partly in the government. UMKM problems often occur due to capital problems and licensing matters, the Business Identification Number (NIB) is the identity of a business license issued by the